A five-year review comparing 30-day mortality following intramedullary nailing versus sliding hip screw for trochanteric hip fractures. Issue 6 (June 2022) - Lynch Wong, M.; Baker, G.; McCusker, D.; Zhang, S.D.; Charlwood, A.P.
Highlights: Recent literature suggests sliding hip screw carries a lower 30-day mortality than intramedullary nailing for intertrochanteric hip fractures. Intramedullary nailing in our study, on the contrary, over a 5-year period carried a lower 30-day mortality. Authors should not be deterred from intramedullary nailing based on previous literature. Rather, intramedullary nailing should be the implant of choice in more unstable fracture patterns. Abstract: Introduction: Recent literature suggests that fixation of trochanteric hip fractures with intramedullary nailing carries a higher 30-day mortality than with sliding hip screw. The present study aims to verify whether this statement is reflected in our practice. Patients and Methods: Sliding hip screw and intramedullary nail fixation of trochanteric hip fractures were analysed over a 5-year period, between April 2011 and March 2016. Three investigators independently analysed 919 patients. Data collected included 30-day mortality, OTA classification of hip fracture and ASA grading. Inclusion and exclusion criteria were applied. Results: 493 patients (66%) underwent sliding hip screw while 252 patients (34%) underwent intramedullary femoral nailing. AO/OTA classification was strongly associated with treatment group. It was found that 30-day mortality rate was 4.8% following intramedullary nailing compared to 6.1% with sliding hip screw. Multivariate logistic regression analysis found ASA grade, male gender and age to be associated with increased 30-day mortality with statistical significance. There was no statistically significant association between treatment group and 30-day mortality, nor between ASA grade and treatment group. Conclusions: Both the lower 30-day mortality rate of 4.8% with intramedullary nailing and the higher rate of 6.1% with sliding hip screw fixation compare favourably with the mean 7.9% National 30-day mortality rate following hip fractures. The lower 30-day mortality in the intramedullary nailing group was not attributable to lower ASA grading nor due to simpler fracture configuration. ASA grade, male gender and age were shown to be statistically associated with increased 30-day mortality. Implications: Previous studies may have deterred surgeons from choosing an intramedullary device. However, we hope this study assists surgeons to make an informed decision on the choice of implant particularly when an intramedullary device is required to provide a more stable construct.